Pelatihan Multiliterasi Pembelajaran Bahasa Melalui Pameran Media berbasis Teknologi di SMKS YAPIM Siak Hulu - Etfita, Fauzul; Alber; Ahmad, Arimuliani; Wahyuni, Sri; Asnawi; Fanjani, Salwa (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
The limited knowledge of students and teachers in multiliteracy-based learning media is one of the obstacles in language learning. Through this community service activity, it is hoped that both parties, teachers, and students, can be more motivated to improve language multiliterate skills. This activity was carried out as a training activity in the form of an exhibition, where several technology-based learning media that could help increase students' multiliteracy were exhibited on banners. This activity was carried out at SMKS YAPIM Siak Hulu Vocational School, with students and language teachers participating. The results of the activity evaluation show that this training is very useful in helping teachers be able to explore ideas, analyze learning needs, design learning models, design learning models, and present learning models. So, in the end, multiliteracy learning can be implemented by utilizing a variety of learning resources and critical literacy stimulation to motivate students.